2001
DOI: 10.1111/j.1349-7006.2001.tb01174.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Periostin, Homologous with an Insect Cell Adhesion Molecule, as a Prognostic Marker in Non‐small Cell Lung Cancers

Abstract: We used our palindromic polymerase chain reaction (PCR)-driven cDNA differential display technique to identify and isolate a gene, designated periostin, from cancer tissues and found it to be overexpressed in several human tumors. We attempted to determine the influence of periostin expression on clinical outcome in patients with non-small cell lung cancer (NSCLC) by reverse transcriptase (RT)-PCR analysis. Periostin gene was highly expressed at the tumor periphery of lung cancer tissue but not within the tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
57
1

Year Published

2004
2004
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(61 citation statements)
references
References 14 publications
3
57
1
Order By: Relevance
“…Periostin is originally identified from osteoblasts and functions as a cell adhesion molecule for preosteoblast and to participate in osteoblast recruitment, attachment and spreading (Takeshita et al, 1993;Horiuchi et al, 1999). Previous studies showed that the expression of Periostin is upregulated in various types of cancer, including head and neck (Gonzalez et al, 2003), colon , Tai et al, 2005, breast , lung (Sasaki et al, 2001c) and ovarian cancer (Gillan et al, 2002). Here, we also found that 68% of OSCC cases expressed Periostin mRNA and 69% of OSCC cases expressed Periostin protein.…”
Section: Discussionmentioning
confidence: 99%
“…Periostin is originally identified from osteoblasts and functions as a cell adhesion molecule for preosteoblast and to participate in osteoblast recruitment, attachment and spreading (Takeshita et al, 1993;Horiuchi et al, 1999). Previous studies showed that the expression of Periostin is upregulated in various types of cancer, including head and neck (Gonzalez et al, 2003), colon , Tai et al, 2005, breast , lung (Sasaki et al, 2001c) and ovarian cancer (Gillan et al, 2002). Here, we also found that 68% of OSCC cases expressed Periostin mRNA and 69% of OSCC cases expressed Periostin protein.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that periostin was up-regulated in various types of cancers such as the lung, 26 brain, 8 ovary, 9 breast, 27 colon 11 and oral cavity, 28,29 and its serum level was reported to be high in patients with thymoma, 30 non-small cell lung cancer 10 and breast cancer. 31 These reports suggested that periostin is involved in tumor spread, invasion and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 Recently, the expression of periostin has been implicated in the development of variety of carcinomas such as neuroblastoma, 8 epithelial ovarian cancer 9 and non-small cell lung carcinoma. 10 Periostin has been also reported to promote the metastatic growth of colon cancer by augmenting cell survival via the Akt/PKB pathway. 11 In addition, periostin has been suggested to promote the invasiveness or growth rate and confer resistance to hypoxia in pancreatic cancer cells, although the source of this protein was stromal cells rather than cancer cells.…”
mentioning
confidence: 99%
“…A similar structure was reported for fasciclin I, a cell adhesion molecule involved in the development of the central nervous system of insects (Zinn et al, 1988), and for the big-h3 molecule, a secreted protein induced by TGF-b1 which promotes the attachment and spreading of fibroblasts (Skonier et al, 1992;LeBaron et al, 1995). Periostin was found to be overexpressed in various types of human cancer such as lung (Sasaki et al, 2001a), brain (Sasaki et al, 2002), ovary (Gillan et al, 2002), breast (Shao et al, 2004) and colon cancers Tai et al, 2005) and elevated levels have been detected in sera of patients with thymoma (Sasaki et al, 2001b), non-small lung carcinoma (Sasaki et al, 2001c) and breast cancer (Sasaki et al, 2003). Although these reports implicate periostin in tumour spread, the functional role of this protein is poorly described and recent publications report conflicting data.…”
Section: Introductionmentioning
confidence: 99%